Energy Devices for Clipless-Sutureless Laparoscopic Appendectomy: A Systematic Review and Meta-Analysis on Utility and Safety - Singh Apoorv; Anand Sachit; Pakkasjärvi Niklas; Verma Ajay; Bajpai Minu (MDPI, 2022)
Background and Objectives: While laparoscopic appendectomy is standardized, techniques for appendiceal stump closure and mesoappendix division remain variable. Novel vessel sealing techniques are increasingly utilized ubiquitously. We sought to systematically summarize all relevant data and to define the current evidence on the safety and utility of energy devices for clipless-sutureless laparoscopic appendectomy in this systematic review and meta-analysis.
Materials and Methods: This review was conducted following the PRISMA guidelines. PubMed, Embase, Scopus, and Web of Science were systematically searched. Inclusion criteria included studies with laparoscopic appendectomy for appendicitis. The intervention included patients undergoing division of mesoappendix and/or securing of the appendicular base using diathermy (Monopolar or Bipolar or LigaSure Sealing Device) or Harmonic Scalpel (Group A) compared to patients undergoing division of mesoappendix and/or securing of the appendicular base using endoclip or Hem-o-lok or ligature (Group B). The methodological quality of the included studies was assessed using the Downs and Black scale. The outcomes of surgical site infection (SSI) or intra-abdominal collection, postoperative ileus, average operative duration, and length of hospital stay (LHS) were compared.
Results: Six comparative studies were included; three were retrospective, two were prospective, and one was ambispective. Meta-analysis revealed a shorter operative duration in Group A with respect to appendicular base ligation (MD -12.34, 95% CI -16.57 to -8.11, p < 0.00001) and mesoappendix division (MD -8.06, 95% CI -14.03 to -2.09, p = 0.008). The pooled risk ratios showed no difference in SSI between groups. Additionally, no difference was observed in LHS. The risk of postoperative ileus was higher in group B regarding mesoappendix division (RR 0.56, 95% CI 0.34 to 0.93, p = 0.02), but no difference was found concerning appendicular base ligation. The included studies showed a moderate-to-high risk of bias.
Conclusions: Clipless-sutureless laparoscopic appendectomy is safe and fast. Postoperative ileus seems less common with energy devices for mesoappendix division. However, the studies included have a moderate-to-high risk of bias. Further studies addressing the individual devices with surgeons of similar levels are needed.